5 - The Informal and Formal Sector Inter-linkages and the Incidence of Poverty in Nigeria: A Case Study of Ilorin Metropolis: DOI: 10.4314/ad.v29i3.22201 - Ijaiya & , Gafar T.; Umar, Chika A. (Africa Development, 2004)
Using a multiple log-linear regression analysis, this paper examines the influence of the inter-relationship between the informal sector and the formal sector of llorin on the incidence of poverty in Ilorin metropolis. The study, carried out using a structured questionnaire to 480 informal sector operators, reported that 200 and 280 of the operators are not poor and poor respectively. Based on those that are poor, their relationship (in terms of the supply of labour, supply goods and raw materials, supply of equipment, provision of financial and technical assistance) with the formal sector is used in determining their influence on the incidence of poverty in Ilorin metropolis. The incidence of poverty thus proxied with their consumption-expenditure. The results obtained (with the exception of the financial linkage) show that the relationship between the informal sector and the formal sector is inversely related to the incidence of poverty, thus confirming our a priori expectations. The paper further suggests measures that would continue to make the informal sector a catalyst for poverty reduction in particular and relevant to the economic development of Ilorin in general.